A lateral distribution function for the radio emission of air showers - Nelles, Anna; Buitink, S.; Corstanje, A.; Enriquez, J. E.; Falcke, H.; Hörandel, Jörg R.; Rachen, J. P.; Rossetto, L.; Schellart, P.; Scholten, O.; Ter Veen, S.; Thoudam, S.; et al. (Proceedings of Science, 2015)
The international LOFAR radio telescope has been used now for four years to detect air showers. Its high antenna density has allowed us to measure the subtle features of the radio emission of air showers. Together with air shower simulations, these data have been used to model the detected signals. The not rotational symmetric footprint is described by an analytical function with as few as four free parameters. The parameters are related to the position of the shower axis, the energy and the distance to the shower maximum. We will show how this parametrization is used for a fast reconstruction of all relevant air shower parameters and what accuracies are obtained in comparison to a full Monte Carlo simulation. We will furthermore elaborate on the absolute scale of our measurements and the predicted signal strengths.
CRIS-Team Scopus Importer:2023-08-15